261OFF-PUMP CORONARY ARTERY BYPASS SURGERY IS ASSOCIATED WITH LOWER CARDIAC DEATH AT 1 YEAR: RESULTS FROM THE ON-PUMP VERSUS OFF-PUMP (ON-OFF) STUDY. (October 2014) - Lemma, M.G.; Piazza, L.; Di Benedetto, G.; Rinaldi, M.; De Paulis, R.; Losito, C.; Rossi, A.; Genoni, M.
Abstract : Objectives: The ON-OFF study has shown that off-pump coronary artery bypass grafting (CABG) reduces early mortality and morbidity in high-risk patients (EuroSCORE ≥6). This is the report of the secondary endpoints. Methods: This multicentre, prospective, randomised, expertise-based, parallel trial enrolled 411 patients for elective or urgent isolated CABG, at 7 Italian and 1 Swiss centres, from 2006 through 2010. The secondary endpoints included both acute events at discharge (atrial fibrillation, intra-aortic balloon pumping and low cardiac output, ventilation >24 h, sternal wound complications, intensive care unit and hospital length of stay) and events at 1 year [overall mortality, major adverse cardiac events (MACE), evidence of myocardial ischaemia]. Results: The rate of MACE at 1 year was 8.2% in the on-pump group and 2.0% in the off-pump group ( P = 0.005), driven by the rate of cardiac death of 5.1% and 1.5% respectively ( P = 0.043). The only significant predictor of cardiac death was the ejection fraction (EF) both at the univariate (EF > 0.5: OR 0.11; 95% CI 0.01–0.87; P = 0.037) and multivariate (EF > 0.5: OR 0.11; 95% CI 0.01–0.88; P = 0.038) analysis. There was no significant difference between on- and off-pump CABG in the rate of secondary endpoints at discharge and in the rate of overall mortality and myocardial ischaemia at 1 year. ECC ( n =195) OPCAB ( n = 200) P -value Cardiac death 10 (5.1%) 3 (1.5%) 0.043 Myocardial infarction 1 (0.5%) 0 0.311 PTCA 5 (2.6%) 1 (0.5%) 0.094 One-year MACE 16 (8.2%) 4 (2.0%) 0.005 ECC, extracorporeal circulation; OPCAB, off-pump coronary artery bypass; PTCA, percutaneous transluminal coronary angioplasty. Conclusion: At 1 year after CABG, there was a significant difference between on-pump and off-pump CABG: the use of on-pump CABG was associated with a higher rate of cardiac death and EF resulted in the only significant and independent predictor of cardiac death.